Standardization of Anthocyanin Compounds in Plants in Indonesia: Literature Review - Agustin, Annastya Eka; Mierza , Vriezka; Annisa, Bunga Nur; Sa’adah, Cantika Nurul; Prasetyo, Fajar; Lubis, Christina Febiola (Sean Institute, 2022)
Anthocyanins are secondary metabolites belonging to the flavonoid group which act as pigments or coloring agents in plants that give red, blue and purple colors to flowers, fruits and vegetables. Anthocyanins have several pharmacological activities such as antioxidants, anti-carcinogenic, preventing impaired liver function, anti-hypertensive, and anti-diabetic. The anthocyanin structure consists of an aglycone form which is sterified by several sugar groups (glycones) and acyl groups in several anthocyanin compounds. In an effort to maintain the standard of a drug made from natural ingredients, the process of standardization of active compounds can be carried out to guarantee and maintain safety, quality uniformity and efficacy. This review was conducted to identify the anthocyanins contained in an extract by means of thin layer chromatography (TLC), UV-Vis spectrophotometer, thin layer chromatography-densitometry, and high performance liquid chromatography (HPLC). The research methodology used is in the form of literature review with reference sources related to the review topic obtained from various sources, such as Pubmed, Science Direct, and Google Scholar.